75.0k views
5 votes
Multiply. (2−5i)(3+i) Enter your answer, in standard form, in the box.

2 Answers

6 votes

Final answer:

To multiply (2−5i)(3+i), distribute each term and combine like terms. The result is 11 - 13i.

Step-by-step explanation:

To multiply (2−5i)(3+i), we can use the distributive property. First, we multiply 2 by both terms in the second parenthesis: 2 * 3 = 6 and 2 * i = 2i. Then, we multiply -5i by both terms in the second parenthesis: -5i * 3 = -15i and -5i * i = -5i^2. Finally, we combine like terms: (6 - 5i^2) + (2i - 15i).

Remember that i^2 = -1. So, we can simplify the expression further: 6 - 5(-1) + 2i - 15i.

Now we can simplify the expression: 6 + 5 + 2i - 15i = 11 - 13i.

User Mahoni
by
5.4k points
6 votes

2*3=6

2*i =2i

3*-5i=-15i

and -5i*i=-5i^2 i^2=-1 so you actually have 5

5-15i+2i+6 simplifies to 11-13i

User Chizou
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.